A driving method for gray scale multiplication of electrowetting display based on hybrid modulation - Mei, Ting; Lin, Zhixian; Xie, Ziyu; Lin, Shanling; Cai, Bipeng; Chen, Mingzhen; Guo, Tailiang (Frontiers in Physics, 2024)
In order to solve the problem of low gray level due to the few driving chips developed based on the photoelectric characteristics of electrowetting display, a driving method based on modulation is proposed to double the gray level of electrowetting display. In this method, the driving waveform based on pulse amplitude modulation and pulse width modulation hybrid modulation is designed, and the gray levelluminance curve of the electrowetting display is measured and analyzed. On this basis, the luminance nonlinear correction is carried out, and the improvement of 64 gray levels to 127 gray levels is realized by the principle of human visual persistence phenomenon. The experimental results show that the proposed driving scheme can break through the limitation of the driving chip and realize the multiplication of gray levels, in which 96% gray levels increase steadily with an average luminance difference of 0.07, and at the same time enhance the contrast and improve the display effect.